Integrating Neurolaw and Principles of Islamic Law: A Scientific Ethical Model of Criminal Responsibility - Fernando, Zico Junius; Hardinanto, Aris; Muksin, Muchlas Rastra Samara; Solehuddin, Solehuddin; Saifulloh, Putra Perdana Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Neurolaw offers an innovative interdisciplinary framework that bridges the gap between neuroscience and legal theory and providing new insights into how human brain influences behavior, intention, and moral decision-making. This study examines the intersection of neurolaw and Islamic law, emphasizing the importance of integrating neuroscience findings, such as brain function, decision-making processes, and mental disorders, into Islamic law’s understanding of criminal responsibility, intention (niyyah), and reasoning (ʿaql). This study demonstrates the potential of neurolaw to strengthen empathy, justice, and an evidence-based legal approach in Islamic law using normative legal research methods through legislative, conceptual, comparative, and futuristic approaches. Furthermore, this study explores how Islamic law’s values of justice, objectivity, and responsibility can serve as ethical guidelines for the responsible use of neuroscience in legal reasoning. Ultimately, this study encourages a careful and principled integration of brain science and Islamic law that maintains fundamental Islamic values while embracing scientific advancements to create a more holistic and humane justice system.